Impact of assay temperature on antibody binding characteristics in living cells: A case study - Encarnação, João Crispim; Barta, Pavel; Fornstedt, Torgny; Andersson, Karl (Biomedical reports, 2017)
Kinetic and thermodynamic studies of ligand-receptor interactions are essential for increasing the understanding of receptor activation mechanisms and drug behavior. The characterization of molecular interactions on living cells in real-time goes beyond most current binding assays, and provides valuable information about the dynamics and underlying mechanism of the molecules in a living system. The effect of temperature on interactions in cell-based assays is, however, rarely discussed. In the present study, the effect of temperature on binding of monoclonal antibodies, cetuximab and pertuzumab to specific receptors on living cancer cells was evaluated, and the affinity and kinetics of the interactions were estimated at selected key temperatures. Changes in the behavior of the interactions, particularly in the on- and off-rates were observed, leading to greatly extended time to reach the equilibrium at 21°C compared with at 37°C. However, the observed changes in kinetic characteristics were less than a factor of 10. It was concluded that it is possible to conduct real-time measurements with living cells at different temperatures, and demonstrated that influences of the ambient temperature on the interaction behavior are likely to be less than one order of magnitude.
Keywords: thermodynamics; real-time interactions; clinical monoclonal antibodies; drug kinetics; growth factor receptors